How Economic Ideas Evolve The Impact of Religion on the German and Italian Welfare State - Hien, Josef (Cambridge Cambridge University Press, 2025)
1. Introduction; 2. Catholicism and the formation of the German welfare state; 3. Catholicism and the Italian Welfare State in the nineteenth century; 4. Protestantism and Catholicism in German postwar reconstruction; 5. The influence of Catholicism on Italian post war reconstruction; 6. What's left? Religion and welfare policies in the twenty-first century in Italy and Germany; 7. Conclusion.
E-Book / Zugriff nur im Lesesaal